Influence of the image levels of distal femur on the measurement of tibial tubercle-trochlear groove distance—a comparative study. Issue 1 (December 2015) - Yin, Li; Chen, Cheng; Duan, Xiaojun; Deng, Bing; Xiong, Ran; Wang, Fuyou; Yang, Liu
Abstract Background The purpose of the present study was to determine whether the image levels of the distal femur affected the measurement of the tibial tubercle-trochlear groove (TT-TG) distance. Methods Thirty sets of computer tomography (CT) images and 30 sets of MR images of the knee were evaluated. The TT-TG distance was quantified at multiple image levels in 1.5-mm increments, covering the proximodistal range of the trochlear groove. The CT measurement was based on osseous landmarks; the magnetic resonance imaging (MRI) measurement was based on cartilaginous and osseous landmarks. Results The average TT-TG distances measured with CT, with MRI based on cartilaginous landmarks, and with MRI based on osseous landmarks were 15.74 mm (SD 3.83 mm), 12.8 mm (SD 5.67 mm), and 12.36 mm (SD 5.58 mm), respectively. No significant difference was found across image levels in the CT measurement and the MRI measurement upon osseous landmarks (P  = 0.64, P  = 0.11); yet, the difference was significant in the MRI measurement upon cartilaginous landmarks (P  < 0.01). Large deviation was found between levels in individual subjects in all the three sorts of measurement. The proximal levels were the most variable, while the mid levels were the least variable. Conclusions Measurements of the TT-TG distance are not identical across the levels of the distal femur. Cautions should be taken when specific image slices were selected for evaluation.